BV/ODV-E26 is a conserved baculoviral inhibitory factor for optimizing viral virulence in lepidopteran hosts - Hiroyuki Hikida; Ryuhei Kokusho; Susumu Katsuma (iScience)
Summary: Alphabaculoviruses induce abnormal behavior in lepidopteran larval hosts. A baculoviral gene, bv/odv-e26, is crucial for behavioral manipulation in Bombyx mori larvae by Bombyx mori nucleopolyhedrovirus (BmNPV). However, how bv/odv-e26 fulfills its role in this phenotype remains largely unknown. In this study, we found that the overexpression of BmNPV bv/odv-e26 delayed viral infection in cultured cells and decreased pathogenicity in B. mori larvae. We also discovered that homologs of bv/odv-e26 are conserved more widely in alphabaculoviruses than previously thought. The inhibitory activity was demonstrated in bv/odv-e26 homologs of phylogenetically close and distant baculoviruses, indicating conserved inhibitory function among alphabaculoviruses. Furthermore, locomotory analyses revealed that bv/odv-e26 increased larval locomotory activity but had little effect on the timing of abnormal behavior initiation. Collectively, our findings demonstrate that bv/odv-e26 is a baculoviral inhibitory factor that is widely conserved in the genus alphabaculovirus and may reduce viral virulence for successful host behavioral manipulation.